Elevation of Plasma Homocysteine and Minor Hallucinations in Parkinson’s Disease: A Cross-Sectional Study - Min Zhong; Sha Zhu; Ruxin Gu; Yaxi Wang; Yinyin Jiang; Yu Bai; Xu Jiang; Bo Shen; Jun Yan; Yang Pan; Jun Zhu; Li Zhang (Behavioural Neurology)
Purpose. Minor hallucinations (MHs) are the most common psychotic phenomena in Parkinson’s disease (PD), and it has important clinical and prognostic implications in PD. Plasma homocysteine (Hcy) has been reported to predict the outcome of PD; whether or not Hcy is associated with MH is not known. We aim to investigate the Hcy level and related factors in patients with PD and MH. Methods. We conducted a cross-sectional study and included 99 patients with PD, 34 with MH, and 65 without any hallucinations. The clinical and demographic data of the patients with and without hallucinations were compared. Hcy-related clinical factors were also analyzed. Results. The plasma Hcy level was higher in MH patients than in patients without hallucinations, and the result was more pronounced in male patients than in female patients. Differences were also observed when the groups were divided on the basis of levodopa equivalent daily dose and disease duration. The high Hcy concentration was correlated with some symptoms in patients with MH, including motor dysfunction and nonmotor symptoms, such as symptoms of the gastrointestinal tract, angiocarpy, sleep/fatigue, and poor visuospatial/executive function. Conclusions. Results indicated a higher plasma Hcy concentration in MH patients than in their counterparts and revealed that Hcy is associated with certain motor and nonmotor symptoms in patients with MH. Hcy may be a marker of MH and have important therapeutic implications in PD.